Schiller und die Slaven - Drews, Peter (Slavistische Beitraege, 2005)
For the first time, this comprehensive study deals with the entire reception of Schiller's works in all relevant Slavic literatures up to 1900. She concentrates on the translations of his poetry into the corresponding languages ​​as well as the respective reactions to his work in scientific circles as well as in the wider literary public. Not least of all, it is taken into account to what extent the respective nationalistic journalistic statements on Schiller reflect an independent Slavic opinion formation or, in their dependence on foreign sources, possibly far more particularly reflect German or French judgments on his work. The presentation complements a detailed, more than 1,600 titles comprehensive bibliography of the transmissions of works Schiller in all Slavic languages ​​until 1900.